A Study on the Alternative Strategies and Approaches to Condense the Security Challenges and Threats Faced in the area of Cloud Computing - Sohail, Habiba; Venugopal, Dhanalakshmi (Journal of Student Research, 2017)
The focal point of this research maneuvers over the challenges and threats that are continuously being faced in cloud computing. Cloud computing is considered as one of the most versatile technology in the recent years. It is an innovative approach towards Information Systems and it has become an integral part of the IT industry. The paper aims to highlight the seriousness of the threats and challenges encountered in cloud computing. In this paper, we give an overview on what makes this technology the future of computing. Immense literature study was conducted to gather adequate data on the recent techniques and terminologies related to the research field. An in-depth research analysis presents a competent mechanism that identifies the challenges and threats in cloud computing. The paper also refers to different security breaches that occurred over the years and what measures were taken to overcome the catastrophic loss. Along with that, it also caters the alternative strategies and approaches available to overcome the possible security threats and challenges. Different alternative methods such as Cryptography and Access Control Mechanisms are identified which are feasible and can be utilized for enhancing the security in cloud computing. Cloud computing is no doubt growing in popularity but even the immensity of this technology cannot disguise the security issues that linger with it. After thoroughly investigating and inspecting all the literary resources, gathered data and information, it is discovered that although cloud computing is tremendously gaining its popularity in the IT field, concerns about its security impact have also been raised considerably. The conclusion of this paper provides different strategies to be adopted to condense the effect of security challenges in the chosen area of the research. Keywords: Access Control, Cloud Application, Cloud Computing, Challenges, Cryptography, Data Portability, Information System, Interoperability, PaaS, SaaS, Security, Threats, Virtualization;